Feasibility of coronary angiography after TAVR. (14th October 2021) - Silva, G; Espada Guerreiro, C; Goncalves Teixeira, P; Ribeiro Queiros, P; Ribeiro Da Silva, M; Brandao, M; Ferreira, D; Pires-Morais, G; Santos, L; Melica, B; Rodrigues, A; Braga, P; et al.
Abstract: Background: The prevalence of coronary artery disease (CAD) is high among patients with severe aortic stenosis who undergo transcatheter aortic valve replacement (TAVR). Indications for TAVR are now expanding to younger and lower risk patients. During their lifetime, these patients will be at risk of developing CAD and it is expected an increase in coronary angiography and percutaneous coronary intervention (PCI). Aortic prosthesis, particularly if in supra-annular position, may pose important technical difficulties in coronary re-engagement after TAVR. Purpose: To evaluate the feasibility to reengage the coronary ostia after TAVR, describe complications and compare technical differences between coronary procedures performed before and after TAVR. Methods: Retrospective analysis of 714 patients submitted to TAVR from August 2007 to December 2019. Patients who needed coronary angiography after TAVR were selected. The primary endpoint was the rate of successful coronary ostia cannulation after TAVR, defined by the possibility to selectively cannulate and inject both coronary ostia. Secondary endpoint was complications associated with coronary catheterization after TAVR. Results: Among 714 patients, 25 (3.5%) patients were submitted to a total of 28 coronary angiography after TAVR. 14 patients were male (56%), mean age 78.2±6.2 years and 9 (36%) had history of previous coronary revascularization. From the 28 coronary angiographies (balloon-expandable Edwards-Sapien n=11, 44%; self-expandable CoreValve n=10, 40%; Portico n=2, 8%; Symetis n=2, 8%), 25 (89%) met the primary endpoint. Only three was semiselective (Symetis, CoreValve Evolut R and CoreValve TAVR in TAVR), with impossibility to cannulate both coronary arteries, right coronary artery and left coronary artery, respectively. 13 (46%) patients had also indication for PCI and all were successfully performed (Edwards-Sapien n=4, 31%; CoreValve n=6, 46%; Portico n=2, 15%; Symetis n=1, 8%). The main indications for coronary angiography was chronic coronary syndrome (n=12, 43%) and acute coronary syndrome without ST segment elevation (n=7, 25%). Circumflex artery was the most frequently treated vessel (n=6), followed by left anterior descending artery (n=4), right coronary artery (n=3) and left main (n=2). There were no complications reported during or post-procedure. Comparing coronary angiographies before and after TAVR, there were no significant differences regarding arterial access site, catheter diameter, fluoroscopy time and quantity of contrast used in coronary angiography. Conclusion: Although the need for coronary angiography was rare in patients after TAVR, selective diagnostic coronary angiographies were possible in 89% (25/28) and PCI was feasible in all patients in whom it was indicated, without any reported complications. Further prospective studies are needed to confirm the great feasibility of performing coronary angiography after TAVR. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Centro Hospitalar Vila Nova de Gaia / Espinho